Factors contributing to urbanization in the heavenly books - Vian Salih Ali; Fathi Jawhar Farmazi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research deals with a study on the factors contributing to urbanization in the heavenly books, by studying the basic factors that help reconstruction, it is not possible to rebuild the earth unless you find it fertile land and this land must have several factors, including reform, cooperation, and the promotion of virtue and the prevention of vice, which help to establish a healthy society. Man is by nature civil and coexists with his own species, so he must prepare the reasons in order to be able to survive among a healthy society. The aim of studying this topic is to show the extent of interdependence between the monotheistic religions through the factors helping in the reconstruction of the earth, every legislation came in order to build an integrated society, and through our study we show the impact of factors on the individual and society, which in turn helps to reconstruct the earth and establish an integrated society, and through that we find the concept of religions for the term reform, work, promotion of virtue, prevention of vice and cooperation on righteousness.